2010
DOI: 10.1111/j.1471-6402.2010.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

I'm No Jezebel; I am Young, Gifted, and Black: Identity, Sexuality, and Black Girls

Abstract: Scholars have highlighted the detrimental influence of racially charged stereotypes and images on self-perception and well being. Others have suggested that identity components (e.g., ethnic identity and self-concept) serve a protective function. The purposes of this study were (a) to explore the relationship among stereotypic images, beauty standards that are consistent with "colorism," and identity components of African American girls and (b) to determine the impact of these variables on girls' sexual attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 47 publications
2
123
0
1
Order By: Relevance
“…23 The MJS is a 20-item measure that assesses black adolescent girls' identification with the various stereotype images that have been constructed about black women. Items for the scale were adapted from the SRBWS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 The MJS is a 20-item measure that assesses black adolescent girls' identification with the various stereotype images that have been constructed about black women. Items for the scale were adapted from the SRBWS.…”
Section: Methodsmentioning
confidence: 99%
“…Results indicated that girls who identified more with stereotypical images of black women in music videos were more likely to emphasize the importance of appearance in their own lives. In addition, Townsend et al 23 explored contemporary stereotype images among African American adolescent girls using the Modern Jezebel Scale (MJS), a modified version of the Stereotypic Roles of Black Women Scale (SRBWS). 24 According to Townsend et al, 23 girls who endorsed the Modern Jezebel stereotype believed that African American girls are highly sexual, aggressive, and even combative.…”
Section: Stereotype Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two African American focused reader's theatre scripts written in 2005 for use at the middle or secondary level were located and are readily accessible (Quinn, 2005;Satchell, 2005). Likewise, there is a body of literature from 2010 to 2011 examining the impact of identity construction on the educational experiences of African American girls during adolescence and high school years, however, much less work exists in the area of pre-adolescence (Brown, 2011;Brooks, Sekayi, Savage, Waller, & Picot, 2010;Hall & Brown-Thirston, 2011;Townsend, Jones, Neilands, & Jackson, 2010). Aside from Buddington's (2000) Clark and Clark-styled (1947) doll study titled, "Barbie.com and Racial Identity," and the research of Belgrave, Chase-Vaughn, Gray, Addison, and Cherry (2000) exploring "The Effectiveness of a Culture-and Gender-Specific Intervention" on increasing resiliency among African American girls, the body of knowledge exploring identity formation among pre-adolescent African American girls is limited.…”
Section: Reader's Theatre: Scripting Bintou's Braidsmentioning
confidence: 97%
“…However, among these small number of studies, findings have been mixed (Beadnell et al, 2003; Lye, Chng, & Gelia-Vargas, 2000; Townsend, Thomas, Neilands, & Jackson, 2010). For instance, among a sample of mostly adult African American, Latino, Asian/Pacific Islander gay males, no relationship was found between ethnic identity and risky sexual behaviors (Lye, Chng, & Gelia-Vargas, 2000).…”
Section: Introductionmentioning
confidence: 99%